2016
DOI: 10.1186/s12931-016-0321-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 and IL-33 induce Type 2 inflammation in basophils from subjects with allergic asthma

Abstract: BackgroundThe alarmin cytokines IL-25 and IL-33 are key promoters of type 2 inflammation. Basophils respond to alarmin cytokines, however the relationship of these cytokines with basophil activation and recruitment in human studies of allergic asthma has not been well characterized. This study investigated the effect of IL-25 and IL-33 on basophils in a model of allergic asthma.Methods10 mild allergic asthmatics underwent allergen and diluent inhalation challenges. Bone marrow aspirates were collected at pre-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 43 publications
2
60
1
Order By: Relevance
“…Sputum samples were induced using hypertonic saline and mucous plugs were selected from samples followed by disbursement with DPBS, as previously described [30]. In brief, sputum samples were centrifuged at 790 g at 4°C for 10 min, followed by the collection of supernatant, centrifugation at 1,500 g at 4°C for 10 min, and aliquoting of supernatant into Eppendorf tubes that were frozen at –20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Sputum samples were induced using hypertonic saline and mucous plugs were selected from samples followed by disbursement with DPBS, as previously described [30]. In brief, sputum samples were centrifuged at 790 g at 4°C for 10 min, followed by the collection of supernatant, centrifugation at 1,500 g at 4°C for 10 min, and aliquoting of supernatant into Eppendorf tubes that were frozen at –20°C.…”
Section: Methodsmentioning
confidence: 99%
“…IL-25 is able to induce promotion of the T H 2 lineage via activation of DCs [35] and is involved in the proliferation of a subpopulation of inflammatory ILC2s [36]. Finally, IL-33 and IL-25 also increase basophil activation and migration in allergic asthma patients [37], and high levels of both cytokines have been reported in bronchoalveolar lavage fluid in asthma models [38].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%
“…It has been shown that allergen provocation is able to increase the expression of IL-25 and its receptor in the asthmatic bronchial mucosa [16] and also the expression of the TSLP receptor on the basophil membrane [9]. Salter et al [8] investigated the effects of the alarmin cytokines IL-25 and IL-33 on basophils in a model of allergic asthma, and found that they increase basophil activation and migratory potential. In our patients, the overexpression of IL-25 and IL-33 on basophils was independent of atopy, which suggests causes other than allergy.…”
Section: Discussionmentioning
confidence: 99%
“…Basophils have an important role in the development of airway inflammation, commonly found in bronchial biopsies of asthmatic patients where their number has been reported to be significantly higher than in healthy subjects [7]. Experimental data show that IL-25, IL-33, and TSLP upregulate the expression of their receptors on the basophil membrane [8,9].…”
Section: Introductionmentioning
confidence: 99%